2011
DOI: 10.4250/jcu.2011.19.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patterns of Left Ventricular Dysfunction in Patients with Pheochromocytoma

Abstract: BackgroundExcessive catecholamine release in pheochromocytoma is known to cause transient reversible left ventricular (LV) dysfunction, such as in the case of pheochromocytoma-associated catecholamine cardiomyopathy. We investigated patterns of clinical presentation and incidence of LV dysfunction in patients with pheochromocytoma.MethodsFrom January 2004 to April 2011, consecutive patients with pheochromocytoma were retrospectively studied with clinical symptoms, serum catecholamine profiles, and radiologic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 22 publications
4
53
0
Order By: Relevance
“…Based on this definition, the prevalence of ACC was 11%, with a takotsubo-like pattern observed in six patients. A previous, smaller series reported three cases of takotsubo-like cardiomyopathy in 36 patients with PPGL 20. In a series of 145 patients with PPGL, Zelinka et al 21 reported cardiovascular complications in 28 cases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on this definition, the prevalence of ACC was 11%, with a takotsubo-like pattern observed in six patients. A previous, smaller series reported three cases of takotsubo-like cardiomyopathy in 36 patients with PPGL 20. In a series of 145 patients with PPGL, Zelinka et al 21 reported cardiovascular complications in 28 cases.…”
Section: Discussionmentioning
confidence: 94%
“…ACC in PPGL may be associated with segmental wall motion abnormalities suggestive of takotsubo cardiomyopathy, also known as stress induced cardiomyopathy or apical ballooning 9 20. In this study, we defined ACC as an acute and life-threatening cardiac condition combining chest pain and/or heart failure, evidence of acute myocardial ischaemia, left ventricular systolic dysfunction, and an absence of significant coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly elevated levels of plasma norepinephrine have already been observed in SIC patients compared to patients with acute myocardial infarction [1]. Furthermore, SIC is prevalent among patients with pheochromocytoma [2] and has been iatrogenically induced by administration of beta adrenergic agonists [3]. All these observations point to circulating catecholamines as the inductors of SIC.…”
mentioning
confidence: 98%
“…5 Because of their ability to hypersecrete catecholamines, PCC and sPGLs can give rise to severe cardiovascular complications, such as shock, myocardial infarction, dissecting aortic aneurysms or heart failure due to toxic cardiomyopathy. [9][10][11][12] In order to avoid these potentially lethal complications, adrenalectomy is indicated for PCC, 13 and with implementation of appropriate preoperative care to modulate the effects of catecholamine release, perioperative mortality is nil. [14][15][16] The pooled incidence of malignant PGL, defined as the presence of metastases, [17][18][19] in populations comprising both unaffected SDHD variant carriers and SDHD variant carriers with manifest nonmalignant PGL is about 8%.…”
Section: Introductionmentioning
confidence: 99%